LINGUISTIC FEATURES OF TRANSLATING MEDIA TEXTS FROM UZBEK INTO ARABIC - Ahmed Jassim Al-Zubaidi (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
The language of journalism is the most worthy of study among linguistic levels, as it represents a form of contemporary Arabic that contributes to shaping and influencing the public's language. The headline is the front page of the text The focus of reducing the laws that its candidate intends, is the first of its kind in modern studies, both in general and in particular, due to its significant role in enriching the language and charging vocabulary with connotations and implications that it has never had before; the infinity of the recipient and his conviction. Hence, the idea of research by studying the headlines of the daily newspaper Okaz, which is one of the largest Kuwaiti newspapers in the Kingdom of Saudi Arabia, and the mouthpiece of the Western Region - which it is currently choosing - as studying the language determines the vision of its external environment, which helps in arriving at a solution to reach the truth, and due to the breadth of the study technique, the creativity of the research is determined in the weekly issue (of the two newspapers in full, starting from 7/2015 to 7/2017 AD. The study methodology My research is descriptive and analytical, based on describing the linguistic reality used in the newspaper. It is interesting to study the language of contemporary daily life, to follow the development that occurred in the classical Arabic language. However, it is also difficult, because the study of the headline in general, and the newspaper headline in particular, is still in its infancy. If it exists, it is theoretical studies that have not been applied to the language of newspaper headlines - as far as I know. The research aims to: 1- Reveal the level of contemporary language used in the headlines of Okaz newspaper. 2- Identify the linguistic features of the newspaper. 3- Identify linguistic errors, due to the seriousness of their prevalence, and reveal their causes, to know the treatment. The research is divided into four sections, preceded by an introduction and followed by a conclusion that crystallizes the results and recommendations, namely: First - A theoretical introduction to the study of the headline. Second - Single linguistic features. Third - Complex linguistic features. Fourth - General features.: Examining the various linguistic features of language used in print media. Comparing different types of texts, their functions, and discourse. Presenting appropriate strategies used in translating media texts. This course aims to study journalistic discourse, focusing on differences in language use in print media, examining current print media and media translation practices, and developing journalistic Terminology.